The in vitro digestibility study of rumen fluid with the supplementation of guava seeds - Ahsanuddin Shah, Suhaimi (2016)
The study on guava seeds have been done for human consumption but it is not widely used yet. In Malaysia, guava fruit is very popular among Malaysian citizen, but how about it seed? The seed mostly will be tossed away and only the flesh of the guava will be eaten. Napier grass is very popular among farmers and is widely used as a livestock feed diet. A study was carry out to see the performance of the guava seed (Psidium guajava) as a supplement towards the main feed diet which is Napier grass (Pennisetum purpureum) in different amount of supplementation which are 2%, 4% and 6%. The proximate analysis which are dry matter (DM), ash, neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL) and crude protein (CP) and also the main study which are in vitro digestibility gas production and in vitro digestibility dry matter (IVDMD) were carried out. 12 samples were collected randomly for Napier Grass and Guava Seeds. Each sample plants were divided into Treatment 1 which consist of 100% Napier Grass (n=3), Treatment 2 consist of 98% Napier Grass 2% Guava Seeds (n=3), Treatment 3 consist of 96% Napier Grass 4% Guava Seeds (n=3), and Treatment 4 consist of 94% Napier Grass 6% Guava Seeds (n=3). The Napier grass was planted at Ladang 2 until 6 weeks old and harvested randomly. The guava seeds were collected from the fruit stalls around Serdang. The result has shown that the dry matter (DM), ash (OM) and crude protein (CP) have the best significant different (p<0.005) than the others which are neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL), in vitro gas production digestibility and in vitro dry matter digestibility (IVDMD). Even though in in vitro gas production digestibility has not shown any significant differences, it still can be applied by adding more percentage of the guava seed as a supplement either 8% or 10% as 6% is not the best amount. As a recommendation, small ruminant feed industry should fully utilise the guava seed which is also known as agriculture by-product as it is low in cost and rich in nutrient content and good for ruminal digestibility.